An extrapolative model of house price dynamics - Glaeser, Edward L.; Nathanson, Charles G. (Journal of Financial Economics, 2017)
A model in which homebuyers make a modest approximation leads house prices to display three features present in the data but usually missing from rational models: momentum at one-year horizons, mean reversion at five-year horizons, and excess longer-term volatility relative to fundamentals. Approximating buyers assume that past prices reflect only contemporaneous demand, just like professional economists who use trends in housing prices to infer trends in housing demand. Consistent with survey evidence, this approximation leads buyers to expect increases in the market value of their homes after recent house price increases.